Artificial Intelligence Methods Applied to Urban Remote Sensing and GIS - Lee, Chang-Wook; Han, Hyangsun; Lee, Hoonyol; Park, Yu-Chul (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is based on Special Issue "Artificial Intelligence Methods Applied to Urban Remote Sensing and GIS" from early 2020 to 2021. This book includes seven papers related to the application of artificial intelligence, machine learning and deep learning algorithms using remote sensing and GIS techniques in urban areas.